АНОМАЛЬНАЯ ЭРОЗИЯ И СТОК НАНОСОВ НА ВОСТОКЕ РУССКОЙ РАВНИНЫ - Сафина Г.Р. (My University, 2004)
Anomalies of annual solid runoff were revealed on the base of annual measurements. They may be divided into three types: small, big and extreme. The main factors of anomalous runoff and erosion were determined for 16 river basins of the east of the Russian Plain. The positive erosion anomalies are more salient in the lesser basins, under stronger human impact on landscape and in more southward regions. The negative anomalies are more distinctive just under reverse conditions. Anomalous manifestations of erosion are of hydro-meteorological origin and have close relation to the other exodynamic processes.
Keywords: 551.435.1(-924.8)